(untitled) (Journal of the Bangladesh Agricultural University, 2012)
Experiments were conducted in the Laboratory and Entomology Field Laboratory to determine the residual effect of two insecticides (viz. Siperin 10EC, Malathion 57EC) and a botanical (Neem oil) against Epilachna beetle, Epilachna vigintioctopunctata (Fab.) during the period from February to May 2009. To evaluate the residual effect of one synthetic and one organophosphors pesticides and one botanical pesticide on the mortality of Epilachna beetle, different concentrations of the insecticides (1.0, 2.0 and 3.0% of Neem oil, 1.0, 1.2 and 1.5% of Malathion and 0.5, 1.0 and 1.5% of Siperin.) was used. The mortality of the beetles was recorded at 4, 5, 6 and 7 days after treatments. After 7 days the highest mortality was found on first instar larvae (70.0 in laboratory condition and 65.0 in field condition) treated by Siperin 10EC (1.5% conc.) and the lowest mortality was found on adults Epilachna beetle (17.5 in laboratory condition and 15.0 in field condition) treated by Neem oil (1.0% conc.) The results indicated that Siperin 10EC has longer residual effect than Malathion 57EC and Neem oil. The effectivity ranked: Siperin > Malathion > Neem oil. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12034 J. Bangladesh Agril. Univ. 10(1): 2125, 2012